Sociocultural Relations of Early Marriage in Sidrap Regency - Arifin, Jamaluddin; Ibrahim Arifin (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
Early marriage in Sidrap Regency is still a worrying phenomenon. Despite various efforts to reduce the number of early marriages, cultural influences, social norms, and economic factors are still strong in encouraging marriage at a young age. This study aims to identify how sociocultural relations affect the practice of early marriage in Sidrap Regency. The method used is a qualitative approach with an exploratory descriptive method. The results of the study show that cultural factors, such as social norms and customs that prioritize marriage as a social obligation, as well as economic pressure, are the main drivers of early marriage. The impact is huge, ranging from the emotional immaturity of couples, the high divorce rate, to the negative impact on reproductive health. In addition, the perception of people who still consider early marriage as a solution to social problems such as pregnancy out of wedlock also worsens the situation. Therefore, preventive efforts involving various parties, such as counseling, increasing access to education, and family economic empowerment, are needed to overcome early marriage in Sidrap.